Analisis Dimensi Dan Peran Aktor Sound Governance dalam Kerja Sama Sister City Pemerintah Kota Surabaya dengan Pemerintah Kota Liverpool (Studi Kasus Pengiriman Sepuluh Pesepakbola Muda Berbakat) - Adalatul Hikmah, Dzakiyah; Prasetyo, Khusnul; Azmy Musaddad, Aditama; Arum Pramestya, Eka; Devi Lestari, Ika (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2022)
This study aims to analyze the dimensions and actors of sound governance in sister city cooperation between the City Government of Surabaya and City Government of Liverpool in the field of sports in order to optimize the potential of Surabaya City youth by sending ten (10) talented youths to Liverpool. The method used in this research is descriptive qualitative with data collection techniques through observation, interviews, literature studies, to documentation. The results showed that of the ten existing sound governance dimensions, the City of Surabaya and the City of Liverpool were able to prove their seriousness in accordance with the cooperation contract that had been translated into a Letter of Intent (LoI) and a Memorandum of Understanding (MoU). In addition, the four sound governance actors, namely the government, the public, the private sector, and the international community, have shown their cooperation and active role although there are several aspects that have not been fully optimized.